HUBUNGAN HARGA DIRI DENGAN BODY SHAMING PADA SISWA KELAS X SMAS AL – WASLIYAH 3 MEDAN - Nur Afni Octaria; Khairina Ulfa Syaimi; Nurul Azmi Saragih; Dina Hidayati Hutasuhut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between self-esteem and body shaming among students. Self-esteem is an individual's evaluation of themselves, influencing how they think, behave, and interact with their environment. Meanwhile, body shaming involves making negative comments or judgments regarding a person's body shape, size, or physical appearance, which can impact an individual's psychological well-being. This study employs a quantitative approach using a correlational method. The study population consists of all Grade X students at SMA Al-Washliyah 3 Medan. A sample of 18 students was selected from a total of 90 using purposive sampling based on criteria established by the researcher. Data collection utilized a Likert-scale questionnaire designed to measure the two research variables: self-esteem and body shaming. Data were analyzed using the Pearson product-moment correlation technique to examine the relationship between the variables. The results indicate a significant relationship between self-esteem and body shaming among students, with a correlation coefficient of r = 0.79 and a significance value of p < 0.05. Based on the interpretation of the correlation coefficient, the relationship between the two variables falls into the moderate category. These findings demonstrate a link between self-esteem and the body shaming experienced by students. Therefore, efforts are required from the school-specifically guidance and counseling teachers-to provide services that boost self-esteem and prevent body shaming behavior within the school environment.